2021
DOI: 10.1021/acsami.1c08832
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of the Thermoelastic Properties of Ultrahigh-Temperature Ceramics

Abstract: Ultrahigh-temperature ceramics (UHTCs) are a group of materials with high technological interest because of their applications in extreme environments. However, their characterization at high temperatures represents the main obstacle for their fast development. Obstacles are found from an experimental point of view, where only few laboratories around the world have the resources to test these materials under extreme conditions, and also from a theoretical point of view, where actual methods are expensive and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…They found that high pressure could enhance the resistance to volume, elastic, and shear deformations of XTiO 3 ceramics. Nath et al [248] . developed an HTC framework for predicting the thermoelastic properties of materials, which combines Taylor expansion and DFT calculations to predict the vibrational free energies of arbitrarily strained structures.…”
Section: Applications Of Htc In Materials Developmentmentioning
confidence: 99%
“…They found that high pressure could enhance the resistance to volume, elastic, and shear deformations of XTiO 3 ceramics. Nath et al [248] . developed an HTC framework for predicting the thermoelastic properties of materials, which combines Taylor expansion and DFT calculations to predict the vibrational free energies of arbitrarily strained structures.…”
Section: Applications Of Htc In Materials Developmentmentioning
confidence: 99%
“…Owing to the much increased computational effort required for such modelling, only relatively few efforts have been directed towards computing temperature dependent elastic constants. They have mostly been limited to FCC [39][40][41], HCP [40,42,43], diamond [44] and body-centred cubic crystals [45,46], while only few works have addressed more complex ceramics [47,48]. But to the best of the author's knowledge, no efforts have been directed towards elucidating the thermal dependence of the elastic constants of hydrides.…”
Section: Introductionmentioning
confidence: 99%
“…High‐throughput materials screening methods are able to identify candidate compositions with desirable properties without time‐consuming trial‐and‐error experimental studies 13–16 . Such methods are especially valuable for investigating the properties of ultra‐high‐temperature ceramics due to the difficulties in testing materials under extreme conditions 17 . For example, atomistic simulations were used to predict the thermal conductivities of ZrC x ceramics with carbon stoichiometries ranging from x = 0.9 to 1 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Such methods are especially valuable for investigating the properties of ultra-high-temperature ceramics due to the difficulties in testing materials under extreme conditions. 17 For example, atomistic simulations were used to predict the thermal conductivities of ZrC x ceramics with carbon stoichiometries ranging from x = 0.9 to 1. 18 The thermal conductivities were predicted to increase with increasing temperature as had been observed in experimental studies.…”
Section: Introductionmentioning
confidence: 99%